Comparison of the effect of 100-meter freestyle swimming and 400-meter running on the electrolytes of short-distance swimmers - Omar Youssef Khalil; Nashwan Ibrahim Al Nuaimi; Omar Alaa El-Din Ahmed (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.